An ontology–based domain model to enhance the software development process. (7th July 2014) - Alias, Mary; Miriam, D. Doreen Hephzibah; Robin, C.R. Rene
As many of the current programming languages provide only a single programming paradigm, most of the software developers need to mix and match different paradigms, which typically leads to an impedance mismatch. To avoid this, it is essential to develop a system which supports a multi–programming paradigm. The proposed system is developed integrating the ontology paradigm in a programming language called Clojure. These ontology paradigms are added as a library in Clojure, for reusability and code sharing. The basic approach used for integrating the systems is metaprogramming. This will craft and process languages for creating, modifying, adapting, adjusting and transforming other programs. The implementation of the ontology paradigm is theoretically based on description logics, which are formalisms for representing knowledge. The developed system will support ontological, functional, object–oriented and concurrent paradigms. The entire business process can be represented using the developed library.